Fair warning [large type] - Connelly, Michael, 1956- (Connelly, Michael, 1956 - Jack McEvoy, 2020)
"Veteran reporter Jack McEvoy has taken down killers before, but when a woman he had a one-night stand with is murdered in a particularly brutal way, McEvoy realizes he might be facing a criminal mind unlike any he's ever encountered. McEvoy investigates--against the warnings of the police and his own editor--and makes a shocking discovery that connects the crime to other mysterious deaths across the country. But his inquiry hits a snag when he himself becomes a suspect. As he races to clear his name, McEvoy's findings point to a serial killer working under the radar of law enforcement for years, and using personal data shared by the victims themselves to select and hunt his targets"--